THE IMPLEMENTATION OF SONG ENGLISH TO IMPROVE STUDENTTS SPEAKING SKILL - Putri Firmansyah, Zulaikha Salsabila; Nurul Awaliyah, Neng Asti; Melinda, Mira (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
This research aims to evaluate the implementation of using English songs as a learning tool in improving students' speaking skills. Speaking skills are an important aspect of foreign language learning, and innovative approaches such as the use of songs can be an interesting and effective way to achieve this goal.This research methodology involved students from various educational levels involved in learning sessions that include English songs. Data was colleted through a questionnaire which included students' level of confidence in speaking English, and their ability to understand pronunciation and accent. The research results show that the use of English songs has a positive effect on students' speaking skills. Most respondents reported that they felt more confident in speaking English after engaging in song learning. They also noted improved understanding of pronunciation and accent. However, this research also identified several challenges faced by students, such as difficulties in understanding songs lyrics and applying the vocabulary they learned from songs into everyday conversations.The result of this study provide additional support of the use English song as an effective learning tool in improving students' speaking skills. Therefore, this research implies the need to develop more efficient learning strategies and more appropriate teaching materials involving songs in the context of English learning in various educational institutions.Keyword: speaking skill, english song, song lyrics, song learning, vocabulary